2021
DOI: 10.1021/acsomega.1c01423
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Causal Link between Peptide Fibrillization and β-Strand Conformation

Abstract: In the prevailing phenomenon of peptide fibrillization, β-strand conformation has long been believed to be an important structural basis for peptide assembly. According to a widely accepted theory, in most peptide fibrillization processes, peptide monomers need to intrinsically take or transform to β-strand conformation before they can undergo ordered packing to form nanofibers. In this study, we reported our findings on an alternative peptide fibrillization pathway starting from a disordered secondary structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…However, not all functionalized RADA16-I achieved good results. Numerous active motifs were covalently bound to RADA16-I, and the result showed that some functionalized RADA16-I showed no activity [ 55 ]. It is believed that the biological function of functionalized scaffolds depends not only on the biological activity of functional motifs but also on the presentation forms of functional motifs, such as mobility, conformation, and orientation.…”
Section: Active Modification Of Rada16-i: Modification With Active Mo...mentioning
confidence: 99%
“…However, not all functionalized RADA16-I achieved good results. Numerous active motifs were covalently bound to RADA16-I, and the result showed that some functionalized RADA16-I showed no activity [ 55 ]. It is believed that the biological function of functionalized scaffolds depends not only on the biological activity of functional motifs but also on the presentation forms of functional motifs, such as mobility, conformation, and orientation.…”
Section: Active Modification Of Rada16-i: Modification With Active Mo...mentioning
confidence: 99%
“…However, not all functionalized RADA16-Ⅰ achieved good results. Numerous active motifs were covalently bound to RADA16-Ⅰ, and the result showed that some functionalized RADA16-Ⅰ showed no activity [56]. It is believed that the biological function of functionalized scaffolds depends not only on the biological activity of functional motifs but also on the presentation forms of functional motifs such as mobility, conformation, and orientation.…”
Section: Motifs From the Extracellular Matrix (Ecm)mentioning
confidence: 99%